Science Learning That Inclusive for Deaf Students in a Pandemic Era: Pembelajaran IPA yang Inklusif Bagi Mahasiswa Tuli di Era Pandemi - Izzatin Kamala; Tsaqifa Taqiyya Ulfah (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2022)
This study aims to describe online learning in science courses for deaf students and the role of peers in science learning in online learning in the inclusion class of the Bachelor Of Education For Islamic Elementary School Teachers Programme. The problem in this study is that there are obstacles experienced by deaf students due to the transformation of the implementation of learning during the covid-19 pandemic. This study uses qualitative methods with data collection techniques in the form of interviews and observations. The results showed that 1) learning during the covid-19 pandemic was carried out online by utilizing several applications that could help deaf students participate in learning, 2) deaf students in science learning could understand the material through material files that had been shared and accompanied by friends. peers and deaf assistants who serve as sign language translators and notetakers, 3) assignments in science learning for all students, both normal and deaf students in the form of papers, video presentations, and practicums accompanied by the role of peers and deaf assistants, 4) if the learning takes place synchronously deaf students do not have assistants, deaf students understand the material independently and are assisted by the google transcript application which functions to convert oral to written, 5) collaboration between lecturers, deaf assistants, and peers is an important element in the implementation of inclusive science learning. Abstrak Penelitian ini bertujuan untuk mendeskripsikan pembelajaran daring pada mata kuliah IPA bagi mahasiswa tuli dan peran teman sebaya dalam pembelajaran IPA pada pembelajaran daring di kelas inklusi Prodi PGMI. Masalah dalam penelitian ini yaitu terdapat kendala yang dialami mahasiswa tuli dikarenakan adanya transformasi pelaksanaan pembelajaran di masa pandemi covid-19. Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data berupa wawancara dan observasi. Hasil penelitian menunjukkan bahwa 1) pembelajaran selama  masa pandemi covid-19, dilaksanakan secara daring dengan memanfaatkan beberapa aplikasi yang dapat membantu mahasiswa tuli agar dapat mengikuti pembelajaran, 2) mahasiswa tuli dalam pembelajaran  IPA dapat memahami materi melalui file materi yang telah dibagikan dan didampingi teman sebaya serta pendamping tuli yang bertugas sebagai penerjemah bahasa isyarat dan notaker, 3) penugasan pada pembelajaran IPA bagi semua mahasiswa baik mahasiswa normal maupun tuli berupa makalah, video presentasi, dan praktikum dengan disertai peran teman sebaya dan pendamping tuli, 4) Jika pelaksanaan pembelajaran berlangsung secara sinkronus mahasiswa tuli tidak ada pendamping, mahasiswa tuli memahami materi secara mandiri dan dibantu aplikasi google transkip yang berfungsi untuk mengkonversi lisan menjadi tulisan, 5) kolaborasi antara dosen, pendamping tuli, dan teman sebaya menjadi unsur penting dalam pelaksanaan pembelajaran IPA yang inklusif.